Improving Children's Mathematical Skills Through the Giant Snake and Ladder Game at Baitul 'Ulum Early Childhood Education Center (Universitas Pendidikan Indonesia Kampus Cibiru, 2024)
This study aims to improve the numeracy skills of early childhood through the giant snakes and ladders game. The subjects of this study were children in GROUP A at an early childhood education center, with 19 participants. This study used a classroom action research (CAR) approach conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. In cycle I, learning was focused on introducing the game and basic counting rules through group activities. The observation results showed that most children began to show interest and involvement in counting activities, although there were still limitations in student attendance. In cycle II, there was a significant increase in children's counting skills, both in counting numbers, sequencing numbers, and recognizing number symbols through game activities. A total of 13 children showed results that developed as expected (BSH). The results of this study indicate that the giant snakes and ladders game is effective in improving the counting skills of early childhood. This game not only stimulates cognitive abilities but also develops children's gross motor and socio-emotional aspects. Therefore, it is recommended that early childhood teachers use similar games as an alternative to make learning arithmetic interesting and enjoyable.